Becoming Jane [videorecording (DVD)] - Jarrold, Julian; Hathaway, Anne, 1982-; McAvoy, James, 1979-; Walters, Julie, 1950- (Miramax Home Entertainment : Distributed by Buena Vista Home Entertainment, 2008)
The young Jane Austen wishes to be a writer. Her mother thinks otherwise. Although she is offered many marriage proposals she accepts none until the mischievous Thomas Lefroy shows up and turns her world around. At first she finds him ignorant and self centered but as she gets to know him, they start to flirt and eventually fall in love. Thomas' relatives disagree with the match and threaten to disinherit him if he marries her. Jane's mother also disagrees with the match. As a result of this, Thomas tries to convince Jane to runaway with him. Instead, Jane stays with her family and ends her affair with Lefroy. She begins to write some of her greatest works of all time. Lefroy becomes the inspiration for Mr. Darcy in the novel, Pride and Prejudice.